THE INFLUENCE OF KNOWLEDGE, INVESTMENT MOTIVATION AND INVESTMENT UNDERSTANDING ON STUDENT INTEREST TO INVEST IN THE CAPITAL MARKET - Suprihati, Suprihati; Pardanawati, Sri Laksmi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The purpose of this study was to determine the effect of understanding on investment interest in the capital market, to determine the effect of investment motivation on investment interest in the capital market and to determine the effect of understanding investment on investment interest in the capital market. The population in this study were ITB - AAS Indonesia students. The sample in this study were 243 students. Collecting data by distributing questionnaires. The data analysis used is multiple linear regression analysis, Anova test, partial test, and model accuracy test. The results of the analysis of this study are understanding investment, investment knowledge, and investment motivation partial and simultaneously influence the interest in investing in the capital market. Keywords: Knowledge, Motivation, Interest, Investment, Capital Market